Profile of retinopathy of prematurity in late preterm newborn in a district level special newborn care unit of Eastern India - Sardar, Syamal Kumar; Pal, Somnath (International Journal of Contemporary Pediatrics, 2018)
Background: The aim of this study was to analyse the incidence, severity and risk factors of retinopathy of prematurity in late preterm newborn at a district level SNCU in eastern India. Methods: The initial examination was carried out at 3 weeks of postnatal age or at 31weeks of post-conceptional age, whichever was later. Retinopathy was graded into stages and zones as per the ICROP classification. Those who had ROP were examined every week till regression occurred or till they reached criteria for laser treatment which was type I Prethreshold ROP as per ET ROP guideline. Risk factors for the development of ROP were determined by reviewing maternal and perinatal history and hospital case records. Results: 212 late ptreterm newborn were examined. The incidence of ROP in late preterm was 16.51% (35 out of 212 newborn). Incidence of stage I ROP was 6.60 % (14 newborn had stage I ROP). Incidence of stage II ROP was 6.60% (14 had stage II ROP). None had stage III ROP. 7 had APROP. Incidence of APROP was 3.30 %. 5 out of 14 newborns with stage II ROP (35.71%) required laser treatment. All newborn with APROP required both laser and Anti VEGF treatment. Overall 34.28% of late preterm with ROP required treatment. There was no difference in gestational age and birth weight in late preterm with and without ROP. There was significant difference in the duration of oxygen therapy in late preterm with and without ROP (6.657±2.531days vs 0.694±1.397 days, p<0.001). In stepwise logistic regression analysis-use and duration of oxygen, birth asphyxia and anemia were found to be significant risk factors of ROP in late preterm. Conclusions: ROP is common in late preterm newborn in developing country like India.